Coal pyrolysis characteristics by TG–MS and its late gas generation potential. (15th September 2015) - Wang, Min; Li, Zhongsheng; Huang, Wenbiao; Yang, Jinxiu; Xue, Haitao
Highlights: Late gas generation potential of coal was investigated by using 1000 °C for TG–MS. Evolution of various gas products was investigated. Late gas generation potential ( v Ro ⩾ 2.5%) of coal is about 17%. The gas generated from 115 to 50 Ma in Shahezi Fm, with no main period of gas generation. Abstract: As natural gas production from deep strata becomes increasingly successful in recent years, the evaluation on gas generation potential from OM (organic matter) in the deep formations is attracting increasing attention recently, especially the late gas generation potential. In this paper, a TG–MS (thermogravimetric analysis–mass spectrometry) device was applied to investigate the process and characteristics of gas generation of HCs (hydrocarbons) and non-HCs (non-hydrocarbons) during the pyrolysis processes of coal from Songliao Basin, and its late gas generation potential. The TG–MS experimental results show that: (1) during coal pyrolysis with heating rate of 10 °C/min, methane generation started at ∼300 °C, reached its peak generation at 480 °C, and ended at ∼850 °C, which was much higher than the ending generation temperatures of other HCs; (2) when investigating the methane generation characteristics through the gas generation curve by ion fragments, more accurate results are obtained with mass to charge ratio m / z = 15 than currently used m / z = 16; (3) this coal has a high late gas generation potential, with 17% additional methane generated at late generation stage after 600 °C (equivalent to a vitrinite reflectance: Ro ⩾ 2.5%), and the methane generation ended at a maturity level of 5.3% (Ro). After calibration with coal pyrolysis results, a kinetic model has been established and applied successfully to estimate gas generation timing and illustrate gas generation mechanisms of the Shahezi Formation in the Xujiaweizi Fault Depression. Based on the results derived from the proposed kinetic model, the gas generation timing for the Shahezi Formation was between ∼115 and 50 Ma, and methane appeared to be generated steadily without any major generation peak indentified during this period and the gas generation lasted for ∼65 Ma.